2018
DOI: 10.1371/journal.pone.0198417
|View full text |Cite
|
Sign up to set email alerts
|

LatY136F knock-in mouse model for human IgG4-related disease

Abstract: BackgroundThe adaptor protein Linker for activation of T cell (LAT) is a key signaling hub used by the T cell antigen receptor. Mutant mice expressing loss-of-function mutations affecting LAT and including a mutation in which tyrosine 136 is replaced by a phenylalanine (LatY136F) develop lymphoproliferative disorder involving T helper type 2 effector cells capable of triggering a massive polyclonal B cell activation that leads to hypergammaglobulinemia G1 and E and to non-resolving inflammation and autoimmunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…Lung lesions of LAT Y136F knock-in mice also had characteristic pathological findings of IgG4-RLD. This was similar to the findings previously described in other organs such as salivary glands, pancreas, and kidney in LAT Y136F knock-in mice [ 23 ], indicating that lung lesions in LAT Y136F knock-in mice are also very similar to IgG4-RD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lung lesions of LAT Y136F knock-in mice also had characteristic pathological findings of IgG4-RLD. This was similar to the findings previously described in other organs such as salivary glands, pancreas, and kidney in LAT Y136F knock-in mice [ 23 ], indicating that lung lesions in LAT Y136F knock-in mice are also very similar to IgG4-RD.…”
Section: Discussionsupporting
confidence: 91%
“…Several animal models of IgG4-RD have been reported [ 19 22 ]. Our previous study using LAT Y136F knock-in mice examined lesions in the pancreas, salivary glands, and kidneys, as well as dural lesions [ 23 ]. Here, we further investigated whether these mice could also constitute appropriate models of lung lesions in IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linker for activation of T cells (LAT) Y136F knockin mouse (LAT mouse) has been reported as a mouse with elevated type-2 T-helper (Th2) cytokine and serum IgG1 (human IgG4-equivalent) levels [10]. In recent years, some reports showed that the LAT mouse could be an animal model of IgG4-RD [11,12]. LAT mice showed IgG1-positive plasmacyte in ltration and brosis in some organs, including the SGs, as well as elevated Th2 cytokine and serum IgG1 [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we established a novel animal model of HP using IgG4‐related disease model mice with a mutation (Y136F) in the linker for activation of T cells (LAT) to investigate therapeutic targets . LAT controls the development and function of T cells by assembling a multiprotein complex following tyrosine phosphorylation .…”
Section: Introductionmentioning
confidence: 99%